Stability of perturbed dynamic system on time scales with initial time difference - Yakar, Coskun; Ogur, Bulent (Tubitak Scientific & Technological Research Council Turkey, 2015)
The behavior of solutions of a perturbed dynamic system with respect to an original unperturbed dynamic system, which have initial time difference, are investigated on arbitrary time scales. Notions of stability, asymptotic stability, and instability with initial time difference are introduced. Sufficient conditions of stability properties are given with the help of Lyapunov-like functions.
Keywords: Time scales; stability; Lyapunov-like functions; comparison results; initial time difference